Pulmonary embolism in patients with the Coronavirus Disease 2019 - Kapała, Przemysław; Versace, Mattia; Tuchendler, Ewelina; Marciniak, Anna; Guzik, Przemysław (Journal of Medical Science, 2022)
Coronaviruses are RNA viruses causing infectious diseases. They had been responsible for 15% cases of a common cold before December 2019. With the new strain of coronavirus SARS CoV2 which causes COVID-19 disease, the ongoing pandemic surprised with the severity of symptoms and its course compared to the previously known mild respiratory tract infections. In the end of December 2021, over 274 million people were diagnosed with COVID-19 disease, and the total mortality amounted to nearly 5.4 million deaths in more than 200 countries. One of the potentially fatal complications of COVID-19 is pulmonary embolism (PE). It appears that PE has been associated with several coagulation abnormalities as well as with frequent significantly elevated concentration of D‑dimer's. A higher D‑dimer concentration in blood serum, in turn, has been associated with an increased risk of premature death. Moreover, inflammation, typical in the course of COVID-19, is considered a prothrombotic condition; higher interleukin 6 (Il-6) and C‑reactive protein concentrations have been found in patients with more severe forms of COVID-19. So far, none specific for COVID-19 studies have been available with regard to the diagnosis and treatment of PE. Therefore, the practical approach is based on the experience of other groups of patients. Prevention of thrombotic events seems reasonable, at least in COVID-19 patients with the risk factors of developing venous thromboembolism. Low‑molecular‑weight heparins are most commonly prescribed (e.g. enoxaparin, dalteparin). Following the confirmed definite PE diagnosis, proper anticoagulation or, if necessary, thrombolytic treatment must be introduced.